Statin Use Decreases the Risk of Metachronous Gastric Cancer in Patients without Helicobacter pylori Infection - Kwon, Tae Jin (Cancers (Basel), 2021)
SIMPLE SUMMARY: Statins have been shown to reduce the risk of gastric cancer (GC). Little is known about their effects on metachronous GC in H. pylori negative patients after endoscopic resection for early gastric cancer (EGC). In this cohort study among patients with EGC without H. pylori infection, we found that statins are associated with a decrease in the risk of recurrence of GC. There was a dose-response relationship between the use of statins and the risk of metachronous GC. This study provides evidence about the additional benefits of statins as chemopreventive agents against metachronous GC among patients who underwent endoscopic resection for EGC. ABSTRACT: Previous studies have shown that statins reduce the risk of gastric cancer; however, their role has not been adequately studied in patients without Helicobacter pylori infection. We aimed to investigate whether statins reduced the risk of metachronous gastric cancer (GC) in H. pylori-negative patients who underwent endoscopic resection for early gastric cancer (EGC). Retrospective data of 2153 patients recruited between January 2007 and December 2016, with no H. pylori infection at baseline, who underwent resection for EGC, were analyzed. Metachronous GC was defined as a newly developed GC at least 1 year after endoscopic resection. Patients who used statins for at least 28 days during the follow-up period were considered as statin users. During a median follow-up of 5 years (interquartile range, 3.5–6.2), metachronous GC developed in 165 (7.6%) patients. In the multivariate Cox regression analysis, statin use was an independent factor associated with GC recurrence (adjusted hazard ratio (HR), 0.46; 95% confidence interval (CI), 0.26–0.82). Moreover, the risk of GC reduced with increasing duration (<3 years: HR 0.40, 95% CI 0.14–1.13; ≥3 years: HR 0.21, 95% CI 0.05–0.90; p trend = 0.011) and the dose of statin (cumulative defined daily dose (cDDD) < 500: HR 0.45, 95% CI 0.16–1.28; cDDD ≥ 500: HR 0.19, 95% CI 0.04–0.80; p trend = 0.008) in the propensity score-matched cohort. Statin use was associated with a lower risk of GC recurrence in H. pylori-negative patients with resected EGC in a dose-response relationship.